PANCASILA SEBAGAI IDEOLOGI BERBANGSA DAN BERNEGARA DALAM PEMIKIRAN INTELEKTUAL MUDA - ARVIDO ABHINAYA TRINANDANA; ARVITO RACHMAN; PUTU ORYZA VARUN P N; RISKA ANDI FITRIONO (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2022)
Pancasila is an ideology held by the Indonesian people as the basis of society. Various circles of society use Pancasila as a basis for doing various things. Pancasila is also expected to be a guide for young people in Indonesia as the nation's next generation and young people must also be able to instill Pancasila values from an early age. focus on their gadgets or cellphones so that they begin to lose the Pancasila values that have been embedded since they were born. This study will discuss how to implement Pancasila values in everyday life, especially from Indonesian youth.